2017
DOI: 10.1002/aenm.201701988
|View full text |Cite
|
Sign up to set email alerts
|

Dual Anion–Cation Reversible Insertion in a Bipyridinium–Diamide Triad as the Negative Electrode for Aqueous Batteries

Abstract: Aqueous batteries are an emerging candidate for low‐cost and environmentally friendly grid storage systems. Designing such batteries from inexpensive, abundant, recyclable, and nontoxic organic active materials provides a logical step toward improving both the environmental and economic impact of these systems. Herein the first ever battery material that works with simultaneous uptake and release of both cations and anions is proposed by coupling p‐type (bipyridinium) and n‐type (naphthalene diimide) redox moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 45 publications
(33 reference statements)
0
43
0
Order By: Relevance
“…Notably,the poly(Te-BnV) anode was able to intercalate 20 Li ions and showed higher conductivity and insolubility in the electrolyte,t hus contributing to ar eversible capacity of 502 mAh g À1 at 100 mA g À1 when the Coulombic efficiency approached 100 %. [12] As ap romising emerging technology for energy storage, [13] ORBs have shown several advantages as compared to previously reported inorganic [14] and polymeric materials, [15] such as no need for rare metals,r eady tunability of redox properties,g reater safety,a nd design flexibility at the molecular level, but the development of such batteries has still been limited. [5] Owing to their synthetic versatility and the ready tunability of their redox properties, [6] the development of viologen-based energy-storage devices has increased dramatically over the past decades.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably,the poly(Te-BnV) anode was able to intercalate 20 Li ions and showed higher conductivity and insolubility in the electrolyte,t hus contributing to ar eversible capacity of 502 mAh g À1 at 100 mA g À1 when the Coulombic efficiency approached 100 %. [12] As ap romising emerging technology for energy storage, [13] ORBs have shown several advantages as compared to previously reported inorganic [14] and polymeric materials, [15] such as no need for rare metals,r eady tunability of redox properties,g reater safety,a nd design flexibility at the molecular level, but the development of such batteries has still been limited. [5] Owing to their synthetic versatility and the ready tunability of their redox properties, [6] the development of viologen-based energy-storage devices has increased dramatically over the past decades.…”
mentioning
confidence: 99%
“…[7] Theexcellent redox properties and unique radical states of viologens make them exceptional electrode candidates for an ew generation of energy-storage devices,s uch as inorganic/organic Li/Na/ Mg ion batteries, [8] aqueous organic redox flow batteries, [9] organic radical batteries, [10] lithium-oxygen batteries, [11] and others. [12] As ap romising emerging technology for energy storage, [13] ORBs have shown several advantages as compared to previously reported inorganic [14] and polymeric materials, [15] such as no need for rare metals,r eady tunability of redox properties,g reater safety,a nd design flexibility at the molecular level, but the development of such batteries has still been limited. [16] Reported ORBs suffered from poor performance,f or example,l ow cell capacity and stability, owing to fewer redox states and low specific energy.T herefore,t he development of novel viologen derivatives with multiple stable redox centers and higher specific energy could dramatically enhance the performance and expand the limits of ORBs.…”
mentioning
confidence: 99%
“…As will be demonstrated throughout this paper, the extended length and specific molecular structure of DNVBr offer us numerous advantages over the first di‐block compound of this kind (referred to as MNV), making it one of the most attractive negative electrode materials for aqueous batteries to date: DNVBr was found to i) support light counteranions (Br − and Cl − ) without dissolving in any of the aqueous electrolytes, ii) display unmatched performance without carbon additive, iii) show an intermixed cation–anion mechanism over almost all of its potential range, and iv) demonstrate outstanding cyclability.…”
Section: Resultsmentioning
confidence: 96%
“…The authors determined that nearly 53 and 32 kW kg −1 materials can be obtained for 1 mg cm −2 electrodes using a 21 m lithium bis‐trifluoromethanesulfonimide water‐in‐salt electrolyte. Lastly, we previously reported a possible new avenue for designing aqueous batteries using an organic material wherein a p‐type viologen and n‐type naphthalene diimide moieties merge together into a short oligomer, thus allowing the exchange of both anions and cations in a narrow potential range, and showing encouraging performance …”
Section: Introductionmentioning
confidence: 99%
“…More recently, the use of viologen derivatives has also proved to be highly promising in the field of electrochemical storage notably as negative electrolyte (soluble state) in aqueous redox flow batteries especially after the impressive results reported independently by Liu's group and Schubert's group . In addition, our group has just demonstrated that viologen‐naphthalene diimide tandem materials give rise to impressive performances in aqueous organic batteries when paired with 2,2,6,6‐tetramethylpiperidinyl‐ N ‐oxyl (TEMPO) derivatives as p‐type positive electrode material . In non‐aqueous media, it is worth noting that to our knowledge only two examples of full p‐type organic batteries are reported in the literature because viologens suffer from a significant solubility in commonly used carbonate‐based liquid electrolytes.…”
Section: Methodsmentioning
confidence: 99%